(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Rural markets have gained importance in the past few years because of the large rise in the purchasing capacity of rural populations brought about by the economy as a whole. In India, the urban and rural markets differ significantly. When compared to urban consumers, rural consumers vary because of family history, wealth, education, as well as other sociodemographic characteristics. The green movement has increased the amount of manufactured and raw products consumed in rural areas. As a result, the market presents potential in the form of a sizable untapped market, rising expendable cash, rising levels of literacy, and broad possibilities for penetration. In order to seize these prospects, a unique marketing approach called "rural advertising" has been developed. Because urban markets have combined with the increasing and relative development has halted, India’s rural marketplaces have undergone substantial adjustments. Marketers have seen the immense potential in rural India, and with authorities focusing more on injecting funds to boost the rural economy, corporations are becoming more eager to establish operations in rural India. Similar to the last paper, this one focuses on the rural market’s position in the Indian economy as well as the potential and challenges it faces in the contemporary, cutthroat marketplace. This essay aims to comprehend the rural market, the significance of rural tourism, and the current state of the rural sector